مبادئ الأمم المتحدة العالمية بشأن سلامة المعلومات - United Nations (United Nations, 2024)
Technological advances have revolutionized communications, connecting people on a previously unthinkable scale. They have supported communities in times of crisis, elevated marginalized voices and helped mobilize global movements for racial justice and gender equality. Yet these same advances have enabled the spread of misinformation, disinformation and hate speech at an unprecedented volume, velocity and virality, risking the integrity of the information ecosystem. New and escalating risks stemming from leaps in AI technologies have made strengthening information integrity one of the urgent tasks of our time. This clear and present global threat demands coordinated international action. The United Nations Global Principles for Information Integrity show us another future is possible.